2007
DOI: 10.1371/journal.ppat.0030087
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Multi-Drug Tolerance and Antibiotic-Induced Responses by the Histone-Like Protein Lsr2 in M. tuberculosis

Abstract: Multi-drug tolerance is a key phenotypic property that complicates the sterilization of mammals infected with Mycobacterium tuberculosis. Previous studies have established that iniBAC, an operon that confers multi-drug tolerance to M. bovis BCG through an associated pump-like activity, is induced by the antibiotics isoniazid (INH) and ethambutol (EMB). An improved understanding of the functional role of antibiotic-induced genes and the regulation of drug tolerance may be gained by studying the factors that reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
154
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(164 citation statements)
references
References 59 publications
10
154
0
Order By: Relevance
“…Our work was complicated by the fact that Lsr2 appears to have an important role in global transcriptional regulation (11). Although we showed that Lsr2 overexpression has a minimal effect on transcriptional control in M. tuberculosis, M. smegmatis lsr2 knockouts do have altered transcriptional responses (11).…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Our work was complicated by the fact that Lsr2 appears to have an important role in global transcriptional regulation (11). Although we showed that Lsr2 overexpression has a minimal effect on transcriptional control in M. tuberculosis, M. smegmatis lsr2 knockouts do have altered transcriptional responses (11).…”
Section: Discussionmentioning
confidence: 82%
“…Many DNA binding proteins locally protect DNA from ROI in vitro, indeed this phenomenon is the basis for DNA foot printing studies (30); thus, one could question the physiological relevance of the in vitro protection which we observed. However, Lsr2 differs from classical DNA binding proteins in its ability to bind long DNA sequences with relative nonspecificity, to oligomerize, and to regulate expression of a large number of genes (11,15). These features, along with its small size and high isoelectric point suggest that Lsr2 is a member of the bacterial histone-like family of proteins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations